Realize Sustainable Corporate Values: Integration of Green Accounting, Corporate Social Responsibility, and Profitability with Good Corporate Governance as A Moderation - Dina Rahayu; R.A Widyanti Diah Lestari; Sumantri (Jurnal Akuntansi, 2025)
This research aims to figure out how using green accounting, putting corporate social responsibility (CSR) into practice, and making money affects how much a business is worth in the long run. Good corporate governance (GCG) can either increase or decrease this effect. This study starts with the idea that companies keep track of their money in old-fashioned ways, but they should be more careful and think about long-term sustainability. This study uses a method that looks at cause and effect using numbers. It gathers data from the yearly reports of manufacturing companies on the Indonesia Stock Exchange from 2019 to 2023. Businesses were chosen through a specific sampling method, and the information was examined using panel data regression with STATA 17 software. The findings from the analysis indicate that green accounting and corporate social responsibility contribute significantly to a company's worth. However, the amount of profit does not have a big impact. The research also discovered that GCG can enhance the influence of green accounting and CSR on a company's worth, but it does not increase the effect on profitability. Overall, this research emphasizes the importance of integrating environmental and social dimensions into business strategy to achieve sustainable firm value, with good corporate governance serving as an essential pillar.